EVALUATION OF ORGANIC VILLAGE WONOKOYO MALANG PLANNING BASED ON LAND ECOLOGICAL ENHANCEMENT (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Urban Vilages are settlements that formed in Urban area without plan. Based of it's structure, the urban villages is one of element that formed the city which is physically on bad condition. This is mainly triggered by overcrowding problem and disorganization of the physical structure of the urban village environment. The absence of a formal structure ini this territorial is due to the absence of a formal spatial arrangement that programmed. Therefore, in urban village arrangement need to find rule-model based of Greenship Neighborhood from Green Building Council Indonesia as well as participation and empowering public to support the formation of villages with more quality and sustainable lives. This research is explanatory research with a qualitative descriptive method that aims to : evaluate the physical characteristics of the organic village of Wonokoyo's environment in Malang City and formulate a structuring model based on the concept of land ecological enhancement which includes :  (1) basic green area, (2) green area for public, (3) habitat conservation, (4) land revitalization, (5) micro climate, and (6) productive land. The results show that the physical characteristics of Wonokoyo village are minimal and the quality of the housing infrastructure is low, where the total land ecological enhancement value is 13 points, from a maximum scale of 19 or 68.42%. The highest value is found in the parameters of the availability of productive land which acts as a provider of vegetables and fruit, as an added value of the existence of the organic village. In order to improve the quality of the settlement of the organic village in Wonokoyo, it is recommended that the arrangement give priority to the parameters of habitat preservation in the form of intervention, local or endemic plants that are in accordance with the village ecosystem.